2019
DOI: 10.1002/adfm.201909537
|View full text |Cite
|
Sign up to set email alerts
|

Facile Anisotropic Deswelling Method for Realizing Large‐Area Cholesteric Liquid Crystal Elastomers with Uniform Structural Color and Broad‐Range Mechanochromic Response

Abstract: Cholesteric liquid crystal elastomers (CLCEs) are soft and dynamic photonic elements that couple the circularly polarized structural color from the cholesteric helix to the viscoelasticity of rubbers: the reflection color is mechanically tunable (mechanochromic response) over a broad range. This requires uniform helix orientation, previously realized by long‐term centrifugation to ensure anisotropic deswelling, or using sacrificial substrates or external fields. The present paper presents a simple, reproducibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
140
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 105 publications
(147 citation statements)
references
References 36 publications
(58 reference statements)
5
140
0
2
Order By: Relevance
“…The network formation corresponds to the kinetic arrest in a drying CNC suspension. While the original anisotropic deswelling method employed long-term centrifugation during solvent evaporation to ensure the required unidirectionality of sample compression [180,181], thereby orienting the helix perpendicular to the resulting elastomer film, we recently demonstrated that the same effect can be achieved without centrifugation if the solution droplet is pinned to the substrate to avoid horizontal compression [182], just as for the case of drying CNC suspensions. Moreover, when a CLCE is stretched in the film plane, perpendicular to the helix axis, the perfect sinusoidal modulation of the optic axis is lost.…”
Section: B Linear Deformation Upon Vertical Compressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The network formation corresponds to the kinetic arrest in a drying CNC suspension. While the original anisotropic deswelling method employed long-term centrifugation during solvent evaporation to ensure the required unidirectionality of sample compression [180,181], thereby orienting the helix perpendicular to the resulting elastomer film, we recently demonstrated that the same effect can be achieved without centrifugation if the solution droplet is pinned to the substrate to avoid horizontal compression [182], just as for the case of drying CNC suspensions. Moreover, when a CLCE is stretched in the film plane, perpendicular to the helix axis, the perfect sinusoidal modulation of the optic axis is lost.…”
Section: B Linear Deformation Upon Vertical Compressionmentioning
confidence: 99%
“…Moreover, when a CLCE is stretched in the film plane, perpendicular to the helix axis, the perfect sinusoidal modulation of the optic axis is lost. Just like for films produced by drying CNC suspensions in which m is not vertical, an alternating arrangement of rapid and slow director rotations results, removing the circular polarization of the reflected light such that the color is seen almost with equal strength through leftand right-handed circular polarizers [182,183].…”
Section: B Linear Deformation Upon Vertical Compressionmentioning
confidence: 99%
“…Previous freely‐standing CLCE films have demonstrated control over color changes through thermal and mechanical strain, yet lack the ability to permanently reconfigure the optical characteristics as demonstrated here. [ 13,18,19 ] We demonstrate both reversible color and shape change through transient application of strain and also permanent reconfiguration of color and shape through photoactivated AFT‐based DCC. [ 20 ] To achieve these outcomes, films were prepared with all the necessary elements; crosslinking, an LCE host, a chiral LC monomer, a radical photoinitiator, and incorporation of AFT‐capable moieties throughout the network.…”
Section: Resultsmentioning
confidence: 99%
“…Other methods to achieve a helicoidal structure use anisotropic deswelling but this process takes ≈8+ hours. [ 13,19,25 ] The approach reported here resulted in a CLCE film with thickness exceeding 50 µm, contributing to variability in alignment but increasing the directionality of observable specular reflection. The resin was cooled between two glass slides to 60 °C, between the broad chiral nematic phase transition temperature of 40 °C and the transition from a chiral nematic to the isotropic phase (T NI ) at 70 °C, as indicated by differential scanning calorimetry (DSC) measurements performed on the resin (Figure S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation